Gravity anomaly grids for the New Zealand region - McCubbine, Jack; Stagpoole, V.; Caratori Tontini, F.; Amos, M.; Smith, E.; Winefield, R. (Taylor & Francis Asia Pacific (Singapore), 2017)
© 2017 The Royal Society of New Zealand. We present 1 arc-minute Bouguer, Faye, free air and topography corrected gravity anomaly grids for the New Zealand region, 25°S to 60°S and 160°E to 170°W. The grids were compiled from existing terrestrial, marine and satellite altimetry-derived gravity data enhanced with new airborne gravimetry data that were acquired for improvement of the New Zealand vertical datum. The airborne data seamlessly cover onshore and offshore areas over New Zealand’s North, South and Stewart islands with a uniform flight line spacing of 10 km. All data were corrected for the gravitational effect of the Geodetic Reference System 1980 (GRS80) reference ellipsoid and tied to the International Gravity Standardization Net 1971 (I.G.S.N.71) gravity datum. The gravity anomaly data from all sources were combined using the method of least squares collocation with a three dimensional logarithmic covariance function. Terrain corrections for gravity anomaly grids were calculated using an 8 m digital elevation model for topography above sea level and a 250 m seafloor topography model.